EXPERIMENTAL COMPARISON OF DIFFERENTIAL-PHASE METHOD AND METHOD OF AUTOFOCUSING IN DEFINING THE ROUGHNESS PARAMETERS OF SURFACE - Стельмах, О.; Бадір, К.; Андреєва, Д. (Science-based technologies, 2010)
In this work is considered differential-phase method and method of autofocusing, which are used on differential-phase laser scanning profilograph-profilometer (DFLSPP) and microscope «MICROSCAN» correspondently. Also is considered experimental comparison of defining of 3D micro- and nano-geometrical surface conditions and standardized roughness parameters of surface with the help of those methods.